A BLACK BOX TESTING DENGAN TEKNIK EQUIVALENCE PARTITIONS PADA WEBSITE DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KARAWANG - Taufik Maulana; Apriade Voutama (Jurnal Sistem Informasi dan Informatika (Simika), 2023)
Website testing is the verification phase whether the website is working properly or not. If there are still errors, they must be corrected so that the website created reaches its goals and is of good quality. The website of the Department of Population Control and Family Planning (DPPKB) of Karawang Regency is being tested. With the name of the website, namely kbinten.id, this website is the official website of the Karawang Regency DPPKB which is used as a place for information about family planning programs in Karawang Regency, which is web-based for the community and consists of two parts, namely the website as an administrative panel and based on the website used by the username. Testing is conducted on a black box utilizing the Equivalence Partitions method. Black box testing allows for an external assessment of the program's functionality without knowledge of the underlying code. The Equivalence Partitions technique is employed to validate data inputted into various forms or pages on the kbinten.id website. Each input value is systematically examined and categorized into test cases yielding either valid or invalid outcomes. The objective of testing on kbinten.id is to identify and rectify implementation errors promptly, thereby expediting the error correction process.